Familial Chylomicronaemia: A Neonate with Milky White Blood - Chaudhary, Nanda Kishwor; Chapagain, Ram Hari; Sipai, Sani; Chaudhary, Suryakant; Paudel, Krishan Prasad (Journal of Nepal Paediatric Society, 2019)
Familial Chylomicronaemia is a rare autosomal recessive disease of lipoprotein metabolism characterized by deficiency or absence of lipoprotein lipase (LPL) or its co-factor apoC-II which causes severe elevation of triglyceride and chylomicron resulting in lipaemic plasma, recurrent attacks of acute pancreatitis, eruptive xanthomas, hepato-splenomegaly and lipaemiaretinalis. We report a case of term female neonate with lipaemic plasma, lipemia retinalis, markedly elevated triglyceride level which is consistent with diagnosis of Familial Chylomicronaemia. Keywords: Familial Chylomicronemia, lipemic plasma, triglyceride level, Lipemia retinalis